Radioactive Starlings : Poems - Hardy, Myronn (Book collections on Project MUSE., 2017)
From an award-winning poet, a collection that explores the complexities of transformation, cultures, and politicsIn Radioactive Starlings, award-winning poet Myronn Hardy explores the divergences between the natural world and technology, asking what progress means when it destroys the places that sustain us. Primarily set in North Africa and the Middle East, but making frequent reference to the poet's native United States, these poems reflect on loss, beauty, and dissent, as well as memory and the contemporary world's relationship to the collective past. Hardy imagines the Portuguese writer Fernando Pessoa as various starlings dwelling in New York City, Lisbon, Tunis, and Johannesburg, flying above these cities, resting in ficus and sycamores and on church steeples and minarets. Inhabiting the invented voices of Gwendolyn Brooks, Bob Kaufman, and Henry Ossawa Tanner, the poems make references to Miles Davis, Mahmoud Darwish, Tamir Rice, Ahmed Mohamed, and Albert Camus, and use forms such as ghazal, villanelle, pantoum, and sonnet, in addition to free lyricism. Through all these voices and forms, the questing starlings persist, moving and observing--and being observed by we who are planted on a crumbling ground. A meditation on the complexities of transformation, cultures, and politics, Radioactive Starlings is an important collection from a highly accomplished young poet.